Multi-Fuel Burner Systems for Industrial Applications - Al-Halbouni, A.; Chalh-Andreas, B.; Hofman, M.; Rahms, H. (Энерготехнологии и ресурсосбережение, 2013)
Multi-fuel firing systems are used in several industrial processes such as in power stations, drying mills and metallurgical plants as well as in rotary kiln systems, industrial boilers, cogeneration plants and various thermal process factories. Such systems should being not only able to utilize different fuel types, but also to respond flexible due to changing in fuel compositions and qualities. In particular the ignition, stability and pollutant problems must be taken into account. That means that these systems should fulfill the operational parameters and ecological target according to German Technical Instructions on Air Quality Control TA Luft 2002. The Operation of these so called multi fuels systems is determined on the one hand by the conditions of the start-up procedure (e. g. drying of the refractory material, creation of the necessary operating environment) and on the other hand by the process-related requirements, fluctuating commodity prices, unstable fuel supplies and the use of internally resulting production scrap. In this paper two multi-fuel burner systems are selected from the extensive Brinkman’s production program to be shown in details. These are combined combustion systems for «pulverized coal-gas» and «pulverized coal-oil», respectively.